INSOMNIA AND ITS ASSOCIATED FACTORS AMONG INDIAN MEDICAL STUDENTS IN VIETNAM: A CROSS-SECTIONAL STUDY USING THE ISI (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe sleep quality and explore associated factors among Indian medical students at Dai Nam University, Vietnam, in 2026.Subjects and methods: A cross-sectional study was conducted in April 2026 among all first-year Indian medical students at Dai Nam University. Of 192 eligible students, 190 participated (response rate: 99.0%). Sleep quality was assessed using the Insomnia Severity Index (ISI). Descriptive statistics were used to summarize the data, while Chi-square tests and independent samples t-tests were applied to examine associations between insomnia and related factors.Results: The mean ISI score was 9.96 ± 6.31 (range: 0–27). Overall, 61.05% of participants were classified as having insomnia (ISI ≥ 8). Mild insomnia was the most common category (39.47%), followed by no insomnia (38.95%), while moderate and severe insomnia accounted for 15.79% and 5.79%, respectively. Insomnia symptoms were mainly reported at mild to moderate levels across all ISI components. No statistically significant associations were observed between insomnia and gender, chronic disease, alcohol consumption, smoking status, GPA, or monthly living expenses (all p > 0.05).Conclusion: Insomnia was highly prevalent among Indian medical students in Vietnam, predominantly at mild to moderate levels. Further studies incorporating psychological and environmental factors are needed to better understand sleep disturbances in this population.
Keywords: insomnia; sleep quality; medical students; international students; Vietnam